A harmonised testsuite for social media POS tagging (DE) - Rehbein, Ines; Ruppenhofer, Josef; Zimmermann, Victor (Universität, 2020)
A harmonised POS testsuite of web data, CMC and Twitter microtext, with word forms and STTS pos tags (+ some additional CMC-specific tags). UD pos ...